2019
DOI: 10.3390/fib7050041
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Polyamide 11 Hybrid Composites Reinforced with Basalt/Flax Interwoven Fibers: A Tough Green Composite for Semi-Structural Applications

Abstract: Intraply hybrid green composites were prepared by film stacking and hot-pressing of bio-based polyamide 11 (PA11) sheets and commercial hybrid fabrics made by interweaving flax and basalt fibers (2/2 twill structure). Two matrices were considered, one of them containing a plasticizing agent. After preliminary thermal and rheological characterizations of the neat matrices, the laminates were studied in terms of flexural properties at low and high deformation rates, and the results were interpreted in the light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…It is worth noting that flax fibre is a very stiff material which has further contributed to this significant flexural properties' improvement. The attainment of such property enhancement with carbon fibre hybridisation provides a significant potential of natural fibre hybrid composites to be used for structural light weight applications [14]. The average flexural properties of three different types of composites are presented in Table 2, and load vs. deformation traces of these composites are shown in Figure 2.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…It is worth noting that flax fibre is a very stiff material which has further contributed to this significant flexural properties' improvement. The attainment of such property enhancement with carbon fibre hybridisation provides a significant potential of natural fibre hybrid composites to be used for structural light weight applications [14]. The average flexural properties of three different types of composites are presented in Table 2, and load vs. deformation traces of these composites are shown in Figure 2.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…Therefore the composite materials can be designed to meet the specific requirements. [10,11] The durability of the basalt mat used as external layers flax reinforced epoxy composites were tested with long-term aging tests which revealed that hybridization of basalt with flax enhances the durability of natural fibers composites. [12] The flax fibers are cheaper and are having low density with better mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their unique characteristics, namely eco-friendliness, light weight, low cost, and high relative strength, these biomass composites have gradually been applied to engineering materials in various industrial applications, such as structural materials and tribomaterials for mechanical sliding parts, such as bearing, cum, gear, and seal, in recent years [ 12 , 13 , 14 , 15 , 16 ]. In particular, to further enhance the eco-friendliness of these biomass polymer composites, fully bio-based polymers such as polylactic acid (PLA) [ 17 , 18 , 19 , 20 , 21 , 22 ] and plant-derived polyamide (PA1010, PA11) [ 12 , 23 , 24 , 25 ] should ideally be used as the matrix polymer. However, these biomass composites have such drawbacks as poor interfacial adhesion between natural fiber and matrix biopolymer [ 3 , 12 , 14 , 26 ] and may, therefore, show poor mechanical and tribological properties.…”
Section: Introductionmentioning
confidence: 99%